2017
DOI: 10.1002/jclp.22486
|View full text |Cite
|
Sign up to set email alerts
|

Emotion Reactivity, Comfort Expressing Emotions, and Future Suicidal Ideation in Emerging Adults

Abstract: Objective: Emotion reactivity and difficulties in expressing emotions have been implicated in risk for suicidal behavior. This study examined comfort in expressing emotions (positive vs. negative) and depressive symptoms as mediators of the prospective relation between emotion reactivity and suicidal ideation. Design: Emerging adults (N = 143; 72% female; 28% White) completed measures of emotion reactivity, comfort expressing emotions, and suicidal ideation at baseline and of depressive symptoms and suicidal i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 53 publications
(74 reference statements)
0
12
0
Order By: Relevance
“…Likewise, there was a significant correlation between higher ER and higher levels of suicidal thoughts and behaviors were highlighted (10). Another longitudinal study indicated that ER predicted suicide risk through depressive symptoms (11).…”
Section: Emotion Reactivity and Suicide Riskmentioning
confidence: 92%
“…Likewise, there was a significant correlation between higher ER and higher levels of suicidal thoughts and behaviors were highlighted (10). Another longitudinal study indicated that ER predicted suicide risk through depressive symptoms (11).…”
Section: Emotion Reactivity and Suicide Riskmentioning
confidence: 92%
“…Psychiatric Services 70:2, February 2019 ps.psychiatryonline.org 111 more likely to perceive an increased risk of suicide related to viewing the series, as well as to strongly identify with the lead characters. This is particularly relevant when considering the evidence for the positive correlation between emotional reactivity and suicidal ideation (38). Concern about the potentially volatile mixture of the emotionally charged content of the series, its highly relatable main characters, and the characteristics of youth viewers in the sample seems warranted.…”
mentioning
confidence: 99%
“…There is also evidence that the valence of the emotion expressed may differentially impact risk for suicidal thoughts (Polanco-Roman et al, 2018) and may be differentially culturally modulated (Chentsova-Dutton et al, 2007; Morelen et al, 2013). For instance, expression of sadness has been found to differ between Asian American (vs. White) depressed adults in response to a sad prompt but not in response to an amusement prompt.…”
Section: Discussionmentioning
confidence: 99%